Montage of Freedom. Phonesia: The Art of Logo-Somatic Articulation through Encounter with Other Livings - Anatoli Vlassov (The February Journal, 2024)
This article delves into the concept of logo-somatic freedom through an analysis of three artworks: Chairs Mots, Diaphoner, and #DanseAvecLesMots. These works exemplify how encounters with ‘other livings’—including language, dance, and digital technology—foster and enrich logo-somatic freedom, transcending conventional boundaries between language, body, artist, audience, and technology. Through practices such as phonesia, participatory performance, and online interaction, the artworks showcase the transformative potential of corporeal poetics and synesthetic communication. The exploration of logo-somatic freedom reveals a perpetual process of metamorphosis in the relationship between body and language, where the deconstruction of logo-somatic expressive habits goes hand-in-hand with the free will of their poetic recomposition. By fostering collective dialogue and individual creativity, these artworks pave the way for innovative forms of artistic expression and collective engagement in the contemporary world. This essay’s exploration of logo-somatic freedom across these artworks highlights its ongoing evolution and its role in shaping the future of artistic expression.